RELATIONSHIP BETWEEN COMPENSATION AND SATISFACTION OF RICE MILL EMPLOYEES AT TINONODO DISTRICT OF EAST KOLAKA - H. Syahrir H. Syahrir; Muhtar Amin; Suprianto Suprianto (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aims to determine the Relationship between Compensation and Satisfaction of Rice Milling Employee at Kecamatan Tinondo East Kolaka (Study of Rice Milling at Kecamatan Tinondo). The study was conducted from April to May 2016. The respondents were drawn at saturated sampling (census) as many as 17 respondents of Rice Milling employees. This research was conducted at a Rice Milling at Kecamatan Tinondo East Kolaka, using quantitative method. Data analysis techniques using Product Moment Correlation with validity test, reliability test and t test with SPSS version 20. The results of the processing of data and discussion shows compensation associated with job satisfaction at 0.662. While the t-test known tcount amounted to 6.398 greater than ttable of 1.745. This means that there is a strong and significant relationship and correlation between compensation and satisfaction of the rice mill employees at Kecamatan tinondo east Kolaka.